Blepharospasm: Update on Epidemiology, Clinical Aspects, and Pathophysiology - Valls-Sole, Josep; Defazio, Giovanni (Frontiers in Neurology, 2016)
Blepharospasm (BSP) is a rather distressing form of focal dystonia. Although many aspects of its pathophysiological mechanisms are already known, we lack fundamental evidence on etiology, prevention and treatment. To advance in our knowledge, we need to review what is already known in various aspects of the disorder and use these bases to find future lines of interest. Some of the signs observed in BSP are cause, while others are consequence of the disorder. Non-motor symptoms and signs may be a cue for understanding better the disease. Various cerebral sites have been shown to be functionally abnormal in BSP, including the basal ganglia, the cortex and the cerebellum. However, we still do not know if the dysfunction or structural change affecting these brain regions is cause or consequence of BSP. Further advances in neurophysiology and neuroimaging may eventually clarify the pathophysiological mechanisms implicated. In this manuscript, we aim to update what is known regarding epidemiology, clinical aspects, and pathophysiology of the disorder and speculate on the directions of research worth pursuing in the near future.